Trolling before the internet : an offline history of insult, provocation, and public humiliation in the literary classics - Rudrum, David, 1974- (New York, USA: Bloomsbury Academic, 2025)
"An accessible and engaging history of trolling before the internet, tracing the ancestry of its textual and rhetorical strategies from ancient Greece to the 20th century. Taking in the contrarianism of Lord Byron, the wit of Oscar Wilde, insult trading in Shakespeare, Jonathan Swift's disaster trolling, Martin Luther's dissemination of heresy through a public discussion forum, the grotesquely misogynistic abuse hurled in Archilochus's poetry, the taunting provocations of avant-garde manifestos, and not forgetting public humiliations in Beowulf, David Rudrum demonstrates that trolls' rhetorical shenanigans are neither new nor unvanquishable"--
Includes bibliographical references and index.
Keywords: Invective in literature; Ridicule in literature; Humiliation in literature; Literary criticism